Implementation of Digital Image Processing to Determine The Body Dimensions of Nile Tilapia Fish - Supriyatna, Agiska Ria; Oktaviana, Adni; Subyantoro, Eko (Politeknik Negeri Bengkalis, 2024)
The present work aimed to use digital image processing techniques for identifying body dimensions of NileTilapia. The total number of exoskeleton measurements made on fish body dimension are high in aquaculture as it is usedto predict the weight, feeding schedule, breeding and market value. Current fish measuring methods can be time-consumingand susceptible to human error. In this research, an automated and effective fish measurement system with digital imageprocessing is proposed. It consists of taking images of the fish, segmenting the fish body from its background and finallyusing contour detection to measure a set of dimensions such as length, height and width. This analysis is applied on thesedimensions to find the weight of specific fish. Overall, the results reveal that the image processing methodology maysuccessfully reproduce manual measurements with a great degree of accuracy and hence can be a suitable tool forapplications in aquaculture practice. This may greatly cut down on operations.